Proposed business strategy for “travorama for business” in business to business market - Adhitia, Rama; Aditya Wibowo, Satya (The Indonesian Journal of Business Administration, 2018)
Abstract - PT Travel Madezy Internasional, which subsequently will be mentioned as TMI in this document, is a relatively new company, established on July 2014. TMI operates in travel e-commerce business using the brand of Travorama (http://www.travorama.com), offering online flight, hotels and travel activities reservation. In the second part of 2016, TMI started the development of new product which was named Travorama for Business. Different from Travorama.com which focuses to sell hotel rooms and flight tickets to retail customer, Travorama for Business is meant to sell hotel rooms and flight tickets to corporate customer. Travorama for Business offer corporate travel management application. This application consists of desktop website, mobile website and mobile app which enables employees to buy flight tickets and hotel rooms online by themselves. This feature improves the productivity of business travel arrangement because employee can make travel arrangements without going through back and forth contact with company administration staff. The purpose of this research is to develop the strategy for Travorama for Business in order to achieve the target market and sustaining the competitive advantage. The research methodology used in this final project is using the qualitative method through the internal interview with the management of Travorama for Business also with potential. The conceptual framework used in this final project arranged by the external analysis and internal analysis of the company. In external analysis using the PESTLE analysis, Porter’s 5 Forces analysis, and competitor analysis. In the other hand, the internal analysis using STP analysis, marketing mix analysis, and the business model canvas analysis. The result of these analysis show several business issues which are lack of brand awareness, the novelty of online travel management concept, a need to expand hotel coverage and flight choice, and finally the high rivalry competition in the industry. The solution offered in this final project is for Travorama for Business to adopt differentiation generic strategy without significantly adding cost.  The strategy formulation starts with doing TOWS matrix analysis. The strategies then are elaborated and expanded further during formulation of the strategy diamond, improvement to 7P marketing mix, and improvement to business model canvas.Keywords:  Corporate Travel, Business Strategy, Marketing Strategy.TOWS Matrix, Strategy Diamond, Business Model Canvas, Marketing Mix